Managerial Accounting in the Unified Accountance System of Decision-Making - Chernikova Irina B.; Kvаshа Olhа O. (Bìznes Inform, 2018)
The article considers many researches in the field of organizing of managerial accounting, that makes it possible to assert that today among scholars there is no single point of view as to definition of managerial accounting, its functions, tasks, attitude to accountance, which, in turn, affects the efficiency of its implementation in the practical activities of Ukrainian enterprises. The main shortcomings associated with the lack of access to management data on strategically important processes occurring in the internal and external environment are defined. It is suggested to unite by segments the conceptual directions of development of today’s accountance through: introduction of managerial accounting; development of new scientific conceptions of accounting; improvement of domestic legislative base in the context of definition of accountance as a system in which accounting information is formed. Recommendations on the use of managerial accounting methods that provide planning and effective control in the implementation of proposed activities in the perspective are provided.